Diagonal Cumulation and Sourcing Decisions - Bombarda, Pamela; Gamberoni, Elisa (World Bank, Washington, DC, 2019)
Products must fulfill predetermined rules of origin to be exported under the preferential access granted by a free trade area member. In turn, rules of cumulation establish which countries' inputs qualify when computing the extent of origin of a product. Recent literature shows that restrictive rules of origin affect sourcing decision by reducing imports of intermediate goods from third countries relative to free trade area partners. This paper uses the introduction of the Pan-European Cumulation System in 1997 to explore the effects of rules of cumulation on trade in intermediate goods. The system provided the European Union Free Trade Area's peripheral partners (''spokes'') the possibility of cumulating stages of production from more countries to qualify for preferential access to the European Union market. Therefore, the system might have altered the organization of production in European Union centric value chains. The paper estimates a triple difference-in-differences specification and exploits different control groups. The results show that the effects of rules of cumulation on trade in intermediates are larger, with the stricter rules of origin applied to the related final good. When switching from bilateral to diagonal cumulation, the analysis finds a reduction in spokes' imports of intermediates from the rest of the world relative to those from spoke, reinforcing value chain connections within the cumulation zone. The analysis also finds a reduction in spokes' imports from the European Union 15 relative to the rest of the world and the Spokes. The findings suggest that the Pan-European Cumulation System allowed a reassessment of sourcing decisions: thanks to the possibility to cumulate, peripheral countries re-organized global value chain links.